Asterossismologia usando dados do TESS de doze gigantes vermelhas com exoplanetas confirmados - Bernardo Pereira Lima Ferreira (2021)
Asteroseismology is the study of oscillations produced in the interior of stars and observed as brightness or radial velocity variations and is a powerful tool for investigating the properties of the stellar structure. In this thesis, we analyze high-precision photometric light curves obtained by the recent TESS space mission for 12 exoplanet host stars that show solar-like oscillations to accurately determine their radii, masses, and ages. Solar-like oscillations are characterized by resonant acoustic modes whose frequencies depend on the properties of the stellar interior. They have an almost constant spacing between modes of adjacent radial order (n) and of a given angular degree (l), which is called the large frequency separation. The mode amplitudes are modulated by a Gaussian envelope, whose center is referred to as the frequency of maximum power. First, we measured the large separation using two independent methods: (a) fitting a Dirac comb to the power spectrum and (b) analyzing a moving window in the spectrum of the spectrum. Then, we estimate the frequency of maximum power after smoothing the frequency spectrum with a broad filter. Finally, we applied the Yale-Birmingham method to determine the radii, masses, and ages of the analyzed stars comparing the asteroseismic parameters, including atmospheric parameters obtained from the literature, with the BaSTI stellar evolution grid models. In summary, we found that the analyzed stars have radii between 3.5 and 10 solar radii, masses between 1 and 2.2 solar masses, and ages between 1 and 11 Gy. They are in the red giant branch (RGB), except for two of them (HD 203949 and 8 UMi) which are on the horizontal branch. Three of the analyzed stars (HD 212771, HD 203949, and Gamma Cep) have already been analyzed and the published results are consistent with ours. For the nine remaining stars (HD 135760, HD 33142, HD 27442, HD 120084, HD 98219, HD 96063, HD 30856, and HD 4732), this work presents their first seismic characterization. Our results for the radii are 3 to 15 times more precise when compared with previous non-seismic analyses. For the masses, the precision is three times larger. In addition, the masses and ages obtained are, in general, smaller and larger, respectively, than those found in other studies, which results from a better differentiation of the models when including the oscillation parameters in the analysis. Our results provide a better estimation of these stars, which allows for a better characterization of their exoplanets.